Risk Factors of Obesity among Children Under 5 Years in Hilla City - Awatif Abd AL-khalik; Ali Hussein Al-Hafidh; Suha Attia Kadhum (Journal of Techniques)
Childhood obesity was rarely seen. But over the past few years, more people have started to see this thing. This issue is mostly attributable to families' shifting lifestyles in the modernized Iraq, where they now have greater spending power, easier access to goods and services, and the means to live more comfortably and opulently because to advancements in technology. A case-control study was conducted on 100 children with obesity and 100 healthy participants in primary health care centers at Hilla city. The study used a convenience sampling technique (non-random sampling technique) to choose the children with obesity and control groups via take body anthropometry and direct interviews. The data collection continued for a period of 3 months starting on 2nd January 2022 and ending on 1st April,2022. The highest percentage of children with obesity in the age group 5 years 36 (36.0%). The mean age was 3.97±0.958, and the range (was 2-5). Fifty percent of children with obesity each for boys and girls. The results found that girl children are likely at higher risk for obesity at 2.125 times than boys. While children whose mothers have low professionals are a likely at less risk for obesity than children who their mother have high professionals (B= -2.065-; P. value< 0.001; OR= 0.127; 95% C.I 0.055-0.291). In addition, a high percentage of obese children gain weight after covid-19. The study revealed female children, mothers with low professional, the mother that gained a high weight during pregnancy, and the heredity of obesity are significantly associated with an increased risk of obesity in children. Health care providers should highlight concerning the risks of obesity and providing prevention strategies, ensuring parental participation by setting policies, guidelines and precautionary measures which should ideally be developed.